Characterization of microstructure and hardening of SiC ceramic brazed joint using TiZrCuNi filler irradiated by He ions. (February 2023) - Sun, Liangbo; Qi, Qin; Liu, Chunfeng; Wen, Yue; Shan, Tipeng; Wang, Shuohao; Zhang, Xinghong; Zhang, Jie
Abstract: SiC ceramic brazed joints for fissile fuel cladding tube have attracted significant interest, but the lack of evaluation of the irradiance resistance has brought serious obstacles to their application in nuclear power. Herein, we propose the experimental study of He-ion irradiation on the interface phases between SiC substrate and TiZrCuNi brazing filler. The microstructure and hardness evolution of each phase at the interface were investigated under different irradiation fluences at room temperature, and the irradiation effects caused by He ion irradiation, such as amorphous and helium bubble, were elucidated. It was revealed that SiC and (Ti, Zr)2 (Cu, Ni) were amorphous with the increase of irradiation fluence, while (Zr, Ti)C was not amorphous but produced a large number of dislocation defects. In terms of irradiation hardening, it was affected by the coupling effect of amorphous and helium bubble defects. Highlights: (Zr, Ti)C reaction layer was formed between SiC ceramic and TiZrCuNi filler during the brazing process. At low irradiation fluence of 1 × 10 16 ions/cm 2, no amorphous phase and He bubbles observed in the joint. When the implantation fluence increased to 1 × 10 17 ions/cm 2, high-density He bubbles appeared in the damage peak region of SiC, (Zr, Ti)C and (Zr, Ti)2 (Cu, Ni) due to the migrating and merging mechanism at room temperature.